Reflexões sobre os saberes locais-globais de professoras de inglês da rede pública - Urvinis, Patrícia (2009)
This research aims at investigating the local-global knowledge which emerges from the discoursive practices of two teachers of English who have just started the course Reflection on Action: the teacher of English learning and teaching and two other ones who have already finished the same course. Our theoretical construct is based on Contemporary Applied Linguistics on the perspective of Moita Lopes (2006a; 2006b; 2002); Kumaravadivelu (2006) and Celani (2005). This study is grounded on the binominal local-global knowledge (Canagarajah, 2005); on the official documents that guide the practice of teachers of English in the Brazilian educational context (São Paulo, 2008; Brasil, 2002; 2000; 1998) and on Vygotsky s Sociocultural and Historical Theory of teaching and learning (Vygotsky, 1930/1989; 1934/2001, among others). The research is conducted by an interpretative methodology (Myers, 1997; Moita Lopes; 1996; Erickson; 1986, among others) and the data has been collected through two instruments: a questionnaire and a semi-structured interview (Rizzini, Castro and Sartor, 1999). For analyzing and interpreting the data, three categories of analysis have been established: the category of thematic content, the observation of how the participants place their enunciates and deontic modalizations (Bronckart, 1997/1999). The study concentrates on three areas of analysis (a) senses, meanings and aims of teachinglearning English in the educational context; (2) planning and criteria for curriculum content selection; and (3) pedagogical practices. The results showed that the teachers who were taking the first module of the course Reflection on Action presented a discourse strongly supported by local knowledge, but heading to a dialogue with a global one. On the other hand, the teachers who have already finished the course achieved more autonomy to reflect about the global knowledge in their relationship to local one to promote the teaching-learning English for specific contexts